A Minimal Set of Sensors in a Smart-Shirt to Obtain Respiratory Parameters. Issue 2 (2020) - Laufer, B.; Murray, R.; Docherty, P.D.; Krueger-Ziolek, S.; Hoeflinger, F.; Reindl, L.; Moeller, K.
Abstract: Smart-Shirts (and other wearable technologies) that provide vital medical data are becoming increasingly prevalent. However, obtaining accurate measurement of respiratory parameters via a Smart-Shirt requires ongoing research. In this study, various respiratory parameters have been captured via an optoelectronic plethysmograph and a body plethysmograph using an optimal set of spatial sensors. Sixty-four reflective markers were fixed on a compression shirt and different respiratory manoeuvres were performed by the subjects. In this analysis, Singular Value Decomposition was used to determine the minimum marker set required to yield accurate predictions of respiratory mechanics. Sufficient accuracy and precision for most clinical applications was able to be determined using positional data from nine markers. Using motions of nine sensors, the tidal volume can be predicted with a mean error of less than 139 ml and an adjusted R 2 higher than 0.96. A subsequent linear regression analysis provides the location of the nine markers. These outcomes reduce the computational complexity of analysing optical based wearable technology, reducing barriers to further uptake.